2012
DOI: 10.1111/1469-0691.12031
|View full text |Cite
|
Sign up to set email alerts
|

Prospective survey of acute osteoarticular infections in a French paediatric orthopedic surgery unit

Abstract: The epidemiology of acute paediatric osteoarticular infections (OAI) has recently evolved, mainly due to the improvement of microbiological diagnosis. We conducted a prospective study to analyse the recent epidemiology and the clinical evolution of paediatric OAI in order to validate the adequacy of our probabilistic first-line antibiotic treatment (intraveinous cefamandole + gentamicin). All children suspected of community acquired OAI were included and followed-up for 3 years. The etiologic diagnosis was bas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
21
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(23 citation statements)
references
References 25 publications
2
21
0
Order By: Relevance
“…Although 24 of all the reviewed cases had specific radiological signs of BJI, only 9 had a positive microbiological culture and were considered definitive diagnoses 15. Our low rate of microbiological identification by standard cultures, similar to the findings in the UK and elsewhere,6 8 20 21 is probably due to the absence of microbiological testing in some patients, the difficulty of growing micro-organisms from bone or joint samples,20 and the absence of PCR for K. kingae detection at that time in our laboratory, which would have increased our rate of microbial identification 22…”
Section: Discussionsupporting
confidence: 78%
“…Although 24 of all the reviewed cases had specific radiological signs of BJI, only 9 had a positive microbiological culture and were considered definitive diagnoses 15. Our low rate of microbiological identification by standard cultures, similar to the findings in the UK and elsewhere,6 8 20 21 is probably due to the absence of microbiological testing in some patients, the difficulty of growing micro-organisms from bone or joint samples,20 and the absence of PCR for K. kingae detection at that time in our laboratory, which would have increased our rate of microbial identification 22…”
Section: Discussionsupporting
confidence: 78%
“…However, following the development of molecular techniques, more recent studies have described K. kingae , a Gram-negative coccobacillus, as the primary pathogen of arthritis, especially in children under 4 years of age 9 10 12 28. In our study, the most common pathogen among 75 children with proven septic arthritis was K. kingae (69% of cases).…”
Section: Discussionmentioning
confidence: 59%
“…(4 cases of septic arthritis and 14 cases of osteomyelitis) of OAI in this study, while (Al-Qwbani et al, 2016) found that the K. kingae is the cause of OAI in majority of cases (septic arthritis 73.1%, osteomyelitis 15.7%, spondylodiscitis 5.4%). A study by Ferroni showed 76.1% of OAI due to K. kingae, while 52.9% of osteomyelitis cases were due to K. kingae in children less than 4 years (Ferroni et al, 2013), this might be attributed to that the patient with Kingella kingae septic arthritis have mild presentation and fewer complication and may not reach to hospital (Basmaci et al, 2011). In addition, septic arthritis cases in this study were few (three) and majority of cases were osteomyelitis (73% of OAI cause by Kingella kingae are septic arthritis) (Al-Qwbani et al, 2016) Another point, child with skeletal system infection in this study were sampled in winter months while K. kingae infection mostly in autumn.…”
Section: Discussionmentioning
confidence: 98%